Аэроупругие колебания лопаточного венца турбомашины в трёхмерном потоке вязкого газа - Гнесин, Виталий Исаевич; Колодяжная, Любовь Владимировна; Жандковски, Р.; Колесник, А. А. (НТУ "ХПИ", 2015)
Представлен метод решения связанной аэроупругой задачи, позволяющий прогнозировать амплитудно-частотный спектр колебаний лопаток в трёхмерном потоке вязкого газа, включая вынужденные, самовозбуждающиеся колебания и автоколебания с целью повышения экономичности и надёжности лопаточных аппаратов турбомашин. Достоверность расчетных результатов подтверждается сопоставлением с экспериментом для 11-й стандартной конфигурации. Численный анализ связанных колебаний подтвердил для данного режима аэродемпфирование при взаимодействии первых шестисобственных форм.

The method used for the solution of the combined aeroelastic problem that allows for the prediction of the amplitude-frequency spectrum of blade vibrations in the three-dimensional flow of the viscous gas including forced self-excited vibrations and self-induced oscillations to increase the efficiency and reliability of the sets of blades of turbine machines has been presented. The viscous gas flow through the blade ring is described by nonstationary Navier-Stokes equations that are presented in the conservative form of conservation laws. A dynamic analysis uses a model approach and finite element analysis to calculate eigenvibrations and vibration frequencies of the blades.
Aeroelastic Vibrations of the Blade Ring of the Turbine Machine in the Three-Dimensional Flow of the Viscous Gas
Keywords: турбоагрегаты; вязкий поток; автоколебания; связанная аэроупругая задача; численное моделирование; selfvibrations; combined aeroelastic problem; numerical simulation